Alternativa de tratamiento y beneficio para la recuperación aurífera, en la planta de beneficio "La López" parroquia Ponce Enríquez, provincia del Azuay. - Apolo, Diego Alberto (2005)
The treatment to be applied to a gold ore depends on its mineralogy and the size at which gold is released. It is necessary first to concentrate the valuable minerals in order to reduce the mass of material. In this way more refined and generally more expensive processes can then be applied to bring the minerals to high purity levels. Mineral processing is the first step in the disposal of bargain material by economical methods. The minerals benefit takes into account the physical and chemical characteristics of the minerals to be recovered, each process is constituted by a series of independent stages, or operational stages within which we can include: comminution, particle classification, solids / solids separation , Solid / liquid separation and metallurgical extraction. The objective of the mineral benefit is to make a product, or concentrate with a high law or the one desired by the buyer and for a low cost of operation. This means that the process must reject the maximum of impurities, maintaining a high level of mineral recovery. All these activities destined to the Treatment and Benefit of the valuable mineral generate impacts to the Environment, most of which are negative for the same, reason why it must be developed in a rational way and seeking a harmony with the natural environment, being fulfilled of this way with The premise of sustainable development and all that implies. This study will serve as documentation that justifies technical, economic and environmental criteria that justify the feasibility of the project.